A sustainable development goal framework to guide multisectoral action on NAFLD through a societal approach. Issue 2 (5th December 2021) - Lazarus, Jeffrey V.; Mark, Henry E.; Colombo, Massimo; Demaio, Sandro; Dillon, John F.; George, Jacob; Hagström, Hannes; Hocking, Samantha; Lee, Nancy; Nieuwenhuijsen, Mark J.; Rinella, Mary E.; Romero‐Gomez, Manuel; et al.
Summary: Background: Non‐alcoholic fatty liver disease (NAFLD) is a highly prevalent condition that requires a comprehensive and coordinated response across sectors and disciplines. Aims: In the absence of a multisectoral framework to tackle this condition, we developed one using the sustainable development goals (SDGs) as the basis for converging thinking about the design and delivery of public health responses. Methods: A multidisciplinary group identified the SDG targets and indicators for inclusion in the new framework through a two‐stage process. Firstly, a core team of three researchers independently reviewed the 169 targets and 231 indicators of the SDGs to select a shortlist. Over two Delphi rounds, a multidisciplinary group of 12 experts selected which of the shortlisted targets and indicators to include. Respondents also provided written feedback on their selection. Targets and indicators with 75% or greater agreement were included in the final framework. Results: The final framework comprises 16 targets—representing 9% of all targets and 62% (16/26) of the shortlisted targets—and seven indicators, accounting for 50% (7/14) of the shortlisted indicators and 3% of all indicators. The selected targets and indicators cover a broad range of factors, from health, food and nutrition to education, the economy, and the built environment. Conclusions: Addressing the challenge of NAFLD will require a re‐envisioning of the liver health landscape, with greater focus on joined‐up systems thinking and action. This new framework can help guide this process, including by outlining the stakeholders with whom the liver health community needs to engage. Abstract : A two‐stage Delphi process to create a NAFLD‐SDG framework.